Community and Consumer Dynamics in NFTs: Understanding Digital Asset Value Through Social Engagement - Kristina Brahmstaedt (Journal of Consumer Behaviour, 2025)
While non-fungible tokens (NFTs) have emerged as a significant blockchain application, research has largely focused on market dynamics rather than consumer behavior. Through in-depth interviews with 21 NFT consumers and a netnographic analysis of Discord interactions (109,517 words), this study develops a comprehensive framework explaining the evolution from initial purchase to sustained or discontinued interest in NFTs. The findings reveal that while profit expectations drive initial purchases, strong community bonds and social identity formation are crucial for maintaining engagement. Specifically, active community participation, both before and after purchases, creates a self-reinforcing cycle where engagement directly influences NFT valuation. However, unfulfilled profit expectations and perceived community abandonment by project leaders often lead to disillusionment. The study extends the Need-to-Belong and Social Identity Theory to the digital asset context, demonstrating how NFT communities serve as platforms for identity expression and emotional support, transcending purely financial motivations. For practitioners, the findings suggest that sustainable NFT projects should prioritize community building and transparent leadership over short-term speculation. This research provides the first longitudinal analysis of NFT consumer behavior, offering insights into how digital assets can create enduring value through social engagement rather than merely speculative trading.
Keywords: 320; blockchain technology; brand community; community-driven consumption; need-to-belong theory; non-fungible tokens (NFTs)